(untitled) (Research, Society and Development, 2020)
This article aims to analyze the socio economic profile of workers who act on the streets of a city’s shopping center. Provides answers about the experiences with the work of merchants from Feira de Santana city. Observations and studies were carried out in the urban perimeter of the city, which lead to identification of areas with the highest concentration of merchants on public roads. Was opted for a field research with the direct application of questionnaire. The treatment of the research disse was based on the studies developed by IBE, DIEESE and OIT. Discussed preliminarily the conceptual aspects of the informality of street work. Considers that street commerce in Feira de Santana contributes to containing the impacts of economic crises, insofar as it maintains income for a weaker section of the feirenses population and also as a job option for workers in several cities in the Northeast region.